Answers

2016-07-18T23:38:45+08:00
First, know that an arithmetic sequence has a common difference in such a way that in an arithmetic sequence: a,b,c; (b-a) should be equal to (c-b). Applying this principle, we would see that:

(5p+12) - (7p+2) = (2p-1) - (5p+12). Then  by simplifying,
 10 - 2p        = -3p - 13
 3p - 2p        = -13 -10
                 p = -23

To check, just substitute -23 into each p. You would get: -159,-103,-47. This is an arithmetic sequence with common difference 56
0
thank you po
ano po yung given ng problem?